Flood Pulse Effects on the Growth of Pseudoplatystoma fasciatum in the Amazon Basin - Luciana Alves Pereira; Leandro Castello; Eric Hallerman; Edson Rubens Ferreira Rodrigues; Carolina Rodrigues da Costa Doria; Fabrice Duponchelle (Fishes, 2024)
Fish growth is a fundamental biological process driven by a multitude of intrinsic (within-individual) and extrinsic (environmental) factors that underpin individual fitness and population dynamics. Interannual variability in river hydrology regarding the intensity and duration of floods and droughts can induce interannual variations in the biotic and abiotic variables that regulate fish growth. However, the understanding of how interannual variability in river hydrology affects fish growth remains limited for most species and ecosystems. We evaluated how inter-annual hydrological variations within the Amazon River basin influence the growth of the catfish Pseudoplaystoma fasciatum. Our research questions were as follows: Do floods lead to the faster growth of P. fasciatum and droughts lead to the slower growth? And do floods and droughts affect all age classes in the same manner? We sampled 364 specimens of P. fasciatum from five sites in the Amazon basin, estimated their growth rates, and related the growth rates to indices of the intensity of floods and droughts. We fitted linear mixed-effects models to test the relationship between growth increments and hydrological indices (with F and D quantifying the intensities of floods and droughts, respectively), age as fixed effects, and basins and Fish ID as random effects. We found an inverse relationship between the increment width in the fish hard parts and hydrological indices. That is, intense floods and droughts negatively affected the growth rates. We also found that the growth of P. fasciatum was no different in years with intense and mild floods across age classes 1–5, although was different for age class 6. However, the growth of P. fasciatum was faster in years of mild droughts for all age classes. Our results showing that the growth of P. fasciatum was slower in years of intense droughts are supported by those of previous studies in the Amazon basin and elsewhere. However, our results showing for the first time that the growth of P. fasciatum is slower in years of intense flooding is the opposite of patterns found in other studies. These results thus suggest that the growth of P. fasciatum is maximized within an optimum range of hydrological conditions, where neither floods nor droughts are intense.